Teaching styles and job involvement in lecturers from a private university at Arequipa (Peru) - Arias Gallegos, Walter L. (2018)
In this article, the relationships between teaching styles and job involvement in lecturers, from a private university of Arequipa City, are valued. For that purpose, 120 university lecturers were tested with Grasha’s Teaching Styles Questionnaire and Lodahl and Kejner’s Job Involvement Scale. The data was compared according to sex, educational level and the profession of the lecturers, correlations and a regression analysis were made in order to value the relationship between the variables of the study. The results indicate that the most predominant teaching styles between the lecturers of the sample were: Expert, Facilitator and Personal model. Moreover, the highest job involvement dimensions were job commitment and job flow. The job involvement was moderately related to the Expert and Personal model teaching styles, but only the Expert style had a positive and significant impact in job involvement.